Smart System Design For Toyota Kijang Super Electrical Cars Based on Microcontroller - Gunandar A; Martinus Martinus (Bandar Lampung University (UBL), 2017)
Electrical system body has a role important in a vehicle that is as the main lighting when traveling at night as well as cues to signal to other drivers when turning and braking and honking horns as one element of safety in a vehicle as a whole. Lighting systems (lighting system) divided into 2 of the lighting system inside and outside lighting system. A microcontroller is a microprocessor that is devoted to instrumentation and control. Microprocessor is a digital electronic device that has inputs and outputs as well as control with a program that can be written and erased in a special way. Microcontroller is a chip in the form of IC (Integrated Circuit) that can receive input signals, process them and provide an output signal in accordance with a program that is loaded into it